The value of anthropometric indices for childhood obesity in Japan - Tsuyoshi Isojima; Susumu Yokoya (Taylor & Francis Group, 2019)
Context: Childhood obesity is one of the most serious public health problems. The simplest method for the identification of adiposity in children involves measuring height and weight because these metrics are easy to obtain and are not greatly affected by observers. Objective: Body mass index (BMI) has been widely used as a surrogate marker of childhood obesity, particularly after the International Obesity Task Force recommended that BMI is appropriate for the determination of childhood obesity. However, in Japan, the percentage of overweight (POW) is more widely used for evaluating childhood obesity. Methods: This review discusses and summarises the situation in Japan regarding the use of various anthropometric indices for assessing childhood obesity, focusing on POW and BMI and including the situation with disease-specific indices. Results: There are two main reasons why POW is widely used in Japan instead of BMI. One reason is that the Japan Society for the Study of Obesity recommended that POW should be used for evaluating childhood obesity. The other reason is that BMI cut-off values for childhood obesity have not been determined in Japan. Conclusion: Individuals involved in child healthcare in Japan should keep in mind both the merits and drawbacks of various anthropometric indices.